Teaching business ethics: Bringing reality to the classroom - Schaupp, Dietrich L. (Journal of business ethics, 1992)
This paper presents an alternative method for discussing ethical issues. The method supports the use of the real world situations and emphasizes the interaction of all constituencies. The method incorporates the use of newspaper reports of real-life occurrences. It also stresses the use of local stories when possible.